Parallel Evolution of C-Type Lectin Domain Gene Family Sizes in Insect-Vectored Nematodes - Ning, Jing; Zhou, Jiao; Wang, Haixiang; Liu, Yaning; Ahmad, Faheem; Feng, Xiaohui; Fu, Yu; Gu, Xiaoting; Zhao, Lilin (Frontiers in Plant Science, 2022)
The dispersal stage of pathogens is crucial for the successful spread and infection of their hosts. Some plant parasitic nematodes have evolved specialized dispersal stages to reach healthy hosts by being carried by insect vectors. Because gene gain and loss is a major factor contributing to the evolution of novel characteristics, it is essential to clarify the gene family characteristics among nematodes with different dispersal modes to disentangle the evolution of insect-mediated dispersal. Here, the size of C-type lectin family genes of insect-vectored nematodes were found to be drastically reduced compared to those of self-dispersing nematodes, whereas the diversity of their functional domains was significantly higher. The gene family sizes of vector-dispersed nematodes were only a twentieth of the size of that of a self-dispersing (i.e. without a biotic vector) nematode model Caenorhabditis elegans, and these genes were inactive during the dispersal stage. Phylogenetic analysis showed that some C-type lectin genes of vector-borne plant parasitic nematodes shared higher homology to the animal parasitic nematodes compared to other plant parasitic nematodes. Moreover, homology modeling predicted that the C-type lectins of insect-vectored nematodes bear remarkable structural similarity to the lectins of their vector’s immune-system. Because C-type lectin genes are important sugar-binding proteins for innate immune response of C. elegans, the loss of some C-type lectin genes of vector-transmitted plant parasitic nematodes might be responsible for their parallel adaptations to a mutualistic relationship with their vector. These results expand our understanding on the evolutionary benefits of vector-mediated transmission for the nematode and vector-nematode co-evolution.